Exploring the implementation of ADR in the Nigerian construction industry - Raji, Barakat Adebisi; Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2017)
Dispute resolution mechanism is a concern phenomenon worldwide for minimising disputes occurring in construction industry. However, disputes can only be minimised and managed through the exploration and establishment of right dispute resolution mechanisms. These mechanisms should be well spelt out in the contract form for parties to explore whenever dispute arises. The nature of dispute dictates the type of mechanism to employ. A dispute may become complex if appropriate mechanism is not employed. Therefore, ADR has a lot to offer in streamlining the dispute resolution mechanisms used for construction dispute resolution in Nigeria. The major part of the study is dedicated to propose reforms in administration of justice in construction disputes in Nigeria. Meanwhile the UK and Malaysia models of ADR for construction dispute resolution are closely studied with a view to proposing practical reforms for dispute resolve in Nigeria. In other to achieve this objective, the research has used questionnaire survey. 600 questionnaires were administered to construction practitioners in Nigeria, out of which 307 useable responses were analysed for this research. This represent 51 % effective response rate. The findings revealed that, the use of ADR mechanism in construction cases can facilitate effective dispute resolution in Nigeria. The implication of the findings presented is this study were discussed in details.